A Trajetória de Internacionalização e seu Reflexo na Aprendizagem Organizacional: Um Estudo de Caso em uma Indústria do Segmento Médico-Odontológico - Iron Lemes (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
This work aims, based on the model of Uppsala, analyze a case to the trajectory of internationalization and your reflection on learning organizational in the involvement of internal units of organization. The information was obtained through semi-structured interviews with managers of indoor units that participated directly or indirectly in internationalization, as well as the analysis of documents and through direct observation. It was found that the trend of internationalization of the company took place in four phases: interest, sporadic export, through representatives and branches; calling attention to the first, differ by the model proposed by Uppsala. As globalization intensifies, there is greater involvement of organizational structure, however, the involvement of internal units is uneven temporally and functionally. Different levels of organizational learning occurred in various stages of internationalization. It was also revealed that some internal units suffered no influence on their learning activity for internationalization.